2021
DOI: 10.1585/pfr.16.2403047
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Nonlinear Modeling of MHD Instabilities for Low-q Plasma on J-TEXT

Abstract: The characteristics of the magnetohydrodynamics (MHD) instabilities for low edge safety factor (low-q) plasma are investigated on J-TEXT with three-dimensional (3D) nonlinear MHD Infrastructure for Plasma Simulation (MIPs) code. The dynamics of m = 2 mode coupling with m = 1 mode is found in the linear growth phase with the initial q axis < 1 equilibrium. And new 3D helical coils are designed for generating additional rotational transform based on the J-TEXT configuration, which is helpful to suppress the ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…For the case with the applied helical coils, the growth rate is far lower than for that without, which implies that the applied helical coils or the externally applied rotational transform have the capability to suppress the MHD modes for the low-q plasma. Further simulation results show that, with the externally applied helical coils, the m=2 mode does not appear and the growth rate of the m=1 mode is much smaller [11].…”
Section: External Rotational Transform Coil Systemmentioning
confidence: 92%
See 2 more Smart Citations
“…For the case with the applied helical coils, the growth rate is far lower than for that without, which implies that the applied helical coils or the externally applied rotational transform have the capability to suppress the MHD modes for the low-q plasma. Further simulation results show that, with the externally applied helical coils, the m=2 mode does not appear and the growth rate of the m=1 mode is much smaller [11].…”
Section: External Rotational Transform Coil Systemmentioning
confidence: 92%
“…The above two kinds of RMP coils can effectively control different TMs in plasma, but cannot effectively increase the stability of the plasma itself. Therefore, in recent years, in order to prevent or avoid the generation and growth of TMs in plasma, a set of helical coils that can provide external rotational transform has been designed on J-TEXT [11]. The helical coils will be put into operation in the near future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the behavior of the kink mode in an external 3D field, it was found that a pair of opposite iota=1 coils can be used to stabilize the kink mode and suppress its growth by adding a small background m=2, n=2 component to the edge magnetic field [53]. Such a coil pair might be used in the near future on J-TEXT to experimentally investigate the stabilization of the low-q regime.…”
Section: Plasma Instability Modelingmentioning
confidence: 99%